NOW’s implementation of the 7Ps of services marketing which led to one of the fastest-growing SMEs - Hossain, S.M Arshad (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.